(untitled) (Gestão & Regionalidade, 2025)
The study aimed to test the application of non-traditional career theories in a context of apparent job stability, but one that involves high technological advances that causes continuous downsizing. The methodological choice was a quantitative investigation, with an exploratory character and a descriptive approach, applied as a survey to 6,405 employees. The results revealed that respondents manage their careers accordingly to the boundaryless career and protean career concepts, which present patterns of flexibility and independence from the organization. They virtually disregard the threat that the technological advances will have upon their work, resulting in the replacement of their work by machines. The study shows that non-traditional theories are also applicable to this type of context.